Redução oclusocervical, mesiodistal e na área dos dentes de pacientes com caninos deslocados por palatino - Camargo, Lilian Souza Kretter de (2011)
The strong correlation between the palatal displacement of canines (PDC) and other dental anomalies indicates the importance of early diagnosis of possible morphological changes to the planning and orthodontic prognosis of affected patients. The objective of this research was to evaluate the possible association of retention changes in the upper canines mesiodistal width, length and area of oclusocervical dental crown of the other permanent teeth. Of a total of 3,045 records, we selected a sample of 134 patients divided into two groups with 67 patients, an experimental group showing palatal displacement of canines (PDC) and a control without any dental anomaly. Panoramic radiographs were used for the diagnosis of displacement of the canines and plaster models used to confirm the diagnosis and analysis of the size of the crowns, measured with digital calipers, the mesiodistal width and length oclusocervical of permanent teeth. The data were subjected to Student's t test (p <0.05) for comparison between groups. It was found statistically significant reduction in the size of dental crowns, in nearly all measures compared to the control group. The more teeth that showed a statistically significant were the second molars, second premolars and lower left canine. The results indicate that palatal displacement of canines (PDC) is presented simultaneously with a reduction of the crowns of other permanent teeth, reinforcing the need for early diagnosis and specific treatment plan, considering this characteristic morphological changes in these dental patients.